2009
DOI: 10.1097/eja.0b013e328324ed2e
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB inhibition provides additional protection against ischaemia/reperfusion injury in delayed sevoflurane preconditioning

Abstract: SPC followed by parthenolide provides a significant protection from I/R injury in this model. As each intervention alone limits NF-[kappa]B activation with I/R, these data are consistent with additive effects of these dual modalities in limiting I/R injury due to NF-[kappa]B activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…IKK-b and subsequent NF-jB activation occurs due to a variety of inflammatory stimuli including viral and bacterial pathogens (Chu et al, 1999). Changes in IKK-b regulation have also been linked to various forms of cancer (Bollrath and Greten, 2009;Hernandez et al, 2010;Karin and Greten, 2005), heart disease (Gupta et al, 2008;Konia et al, 2009) and to the development of type II diabetes (Arkan et al, 2005). Recently IKK-b has been characterised as a novel drug target against influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…IKK-b and subsequent NF-jB activation occurs due to a variety of inflammatory stimuli including viral and bacterial pathogens (Chu et al, 1999). Changes in IKK-b regulation have also been linked to various forms of cancer (Bollrath and Greten, 2009;Hernandez et al, 2010;Karin and Greten, 2005), heart disease (Gupta et al, 2008;Konia et al, 2009) and to the development of type II diabetes (Arkan et al, 2005). Recently IKK-b has been characterised as a novel drug target against influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…*Significantly (p \ 0.05) different from CON group after reperfusion, n = 4 per group mechanisms have been extensively studied such as K ATP channel, NF-jB, 12-lipoxygenase and so on [5][6][7], but very few studies have focused on the role of apoptosis in delayed APC. Studies demonstrated that APC with sevoflurane protects myocardium from I/R not only protects myocardial by reduced infarct size, but also improves cardiac functional recovery, decreases post-ischemic myocardial stunning and attenuates myocardial apoptosis [3,8,18,19]. In this study, we focused on the apoptosis induced by myocardial I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Kehl et al [13] reported that, unlike ischemic preconditioning, isoflurane does not produce a second window of protection (SWOP) 24 h after administration in dogs. However, others have reported that isoflurane has delayed cardiac protective effects using in vivo mouse myocardial I/R model [6] and delayed APC with sevoflurane has a similar effect on myocardial protection [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations